Apakah Youtuber Indonesia Kena Bully Netizen? - Joviano Siahaan; Wella Wella; Ririn Ikana Desanti (ULTIMA InfoSys, 2020)
This study will examine the cyberbullying phenomenon that was experienced by Indonesian Youtubers in their Instagram comment section. Cyberbullying is the use of electronic communication to bully a person, typically by sending messages of an intimidating or threatening nature. Youtubers are the subject of this research due to their massive following, who constantly responds to every content posted on their Instagram page. The algorithm chosen to conduct this sentiment analysis was Support Vector Machine (SVM) due to their high accuracy percentage. The data used in this analysis was retrieved from 10 Indonesian Youtuber Instagram accounts. In order to analyze this data, several step was done including text mining, data cleansing, data modeling and applying model to test data. The result of analysis using an SVM model with an accuracy of 81.2% is 49.524% of comments on an Indonesian Youtuber comment section are considered as cyberbullying.